P19 Developing a framework for priority setting in an integrated health and social care setting. (September 2018) - Collins, M; Baker, R; Mazzei, M; Morton, A; Frith, L; Syrett, K; Leak, P; Donaldson, C
Abstract : Background: There is a move, internationally, towards greater integration of health and social care. Integration, it is argued, should reduce budgetary boundaries and facilitate sharing of resources across health and social care. At local levels, delivery organisations need to alter the balance of care from acute settings to people's own home or similar community environments against a background of increasing austerity. To facilitate this shift, there is a need to use robust processes for allocating resources to make difficult decisions and to create interdisciplinary priority setting frameworks involving economists, ethicists, lawyers and decision scientists. In 2014, the Scottish Government established Health and Social Care Partnerships (HSCPs) to deliver this agenda, creating single commissioners and unifying budgets. This paper presents the early stages of a research project funded by the Chief Scientist Office, part of the Scottish Government Health Directorates with the aim to develop and implement an enhanced, multi-disciplinary framework for priority setting, for use by 4 HSCPs, and assess its impact on decision-making and resource allocation. Methods: To develop the framework, a literature review was conducted and the combined framework presented to a multi-disciplinary workshop involving academic colleagues, local and national-level stakeholders to gain feedback to develop it further. Participatory Action Research is being undertaken to explore how the framework functioned within complex settings, and how HSCP participants engaged with the framework, and consider how the framework can be adapted to the institutional setting as well as vice versa. Before and after interviews will be conducted. Results: The framework is underpinned by principles from economics (opportunity cost), decision-analysis (good decisions), ethics (justice) and law (fair procedures). It includes key stages for those undertaking priority setting to follow, including: framing the question, looking at current use of resources, defining options and criteria, evaluating the options and criteria and a review stage. Each of these has further sub-stages and it includes a focus on how the content of the process and the framework interacts with the consultation and involvement of patients, public and the wider staff. Discussion: To assess its impact, the four sites using the framework will be compared with the remaining 27 HSCP sites. The aim of the comparison is to establish: the extent to which the remaining sites use elements of the framework; the principles and processes used for decision-making, and whether decisions have resulted in evidence-based resource shifts.